Freeze-Etching of the Cell Envelope of an Acinetobacter Species Which Carries a Regular Array of Surface Subunits - Sleytr, U. B. (1973)
Freeze-etching was applied to preparations, with and without glycerol, of Acinetobacter sp. strain MJT/F5/199A, consisting of intact cells after normal growth or after incubation with chloramphenicol, spheroplasts, and isolated cell walls and outer membranes. Etched preparations show that a regular array of subunits forms the surface of normal cells. Near the zones of constriction in dividing cells, blebs and irregularities are seen, and some blebs, consisting of both surface subunits and outer membrane, are released from the cells. The cross-fractured cell envelope shows four layers which are related to the structures seen in section as follows: cw1, which is not visible in section, contains the surface subunits; cw2 consists of all or part of the outer membrane; cw3 includes the intermediate and dense, peptidoglycan-containing layers; within these cell wall layers is the plasma membrane. Internal fracture of the plasma membrane occurs under all conditions tested, but the fracture plane in the cell wall is only revealed in chloramphenicol-treated cells or normal cells freeze-fractured with glycerol present; the characteristic fracture faces are not seen in spheroplasts or isolated outer membranes. The concave fracture face c̆w2 consists of densely packed granules, while the convex face c̆w3 is fibrillar. The probable location of this fracture plane is discussed. After incubation with chloramphenicol, the outer surface of the cells is obscured by extracellular material, the dense peptidoglycan-containing layer is increased in thickness, and the cytoplasm contains rounded bodies bounded by one or more unit membranes.